Guiding Policy Through Workload Indicators: A Study of Three Orthopaedic Units - Rahman, Obaid Ur; Hanif, Muhammad; Wahab, Abdul; Hassan, Muhammad; Hidayat, Yasir; Riaz, Saad (Journal of Rawalpindi Medical College, 2026)
Objective: To estimate staffing and resource requirements in Pakistan for Orthopaedic units of three Allied Hospitals in a major city, Rawalpindi, using Workload Indicators of Staffing Needs (WISN). To identify inequitable resource distribution and consequently implement and audit improvements. Recheck the change brought after a period of two years in the same three Orthopaedic units. Methods: Human resources and Workload across the Orthopaedic units of three tertiary-care Hospitals in Rawalpindi in the year 2021 were assessed. Anonymous institutional data was analyzed using WHO’s WISN methodology. Metrics included: Staffing levels (specialists) Workload (surgeries, admissions, outpatient, teaching hours). WISN calculations: Standard Workload, Work in Facility, and Staffing Requirements. These calculations were used to identify the deficits or surpluses of human resources in the three hospitals. Based on this data, we tried to adjust the staff within the three hospitals. These adjustments were limited due to various constraints in public hospitals. Similar data was again collected in the year 2023, and any change [positive or negative] between 2021 and 2023 was assessed using the same parameters. Results: In the year 2021, the total number of patients treated in all Orthopaedic units was 104760, with Hospital A managing 11.4%, Hospital B 67%, and Hospital C 21.6% of the patient load. The number of specialists in hospitals A, B, and C was 8, 8, and 2, respectively. WISN Scores: Hospital A: 3.64 (overstaffed, 5 surplus specialists). Hospital B: 0.99 (optimal staffing). Hospital C: 0.65 (35% deficit; requires +2 specialists). In the year 2023, the total number of patients treated in all Orthopaedic units was 93908, with Hospital A managing 12% of the patient load, Hospital B 67%, and Hospital C 21%. The number of specialists in hospitals A, B, and C was now 5,6,4 respectively. WISN Scores: Hospital A: 2 (overstaffed; 3 surplus specialists). Hospital B: 0.77 (understaffed: requires +2 specialists). Hospital C: 1.3 (1 surplus specialist). Conclusion: WISN effectively highlighted staffing imbalances in 2021, with Hospital C grossly understaffed and Hospital A heavily overstaffed. Reallocation of surplus staff based on figures forthcoming from this study improved equity in 2023, though Hospital B’s emerging deficits underscore the need for dynamic workforce planning. WISN has proven to be an effective tool in the hands of policymakers for evidence-based resource allocation in public health systems. Keywords: Workload, Orthopaedic Units, Staffing Needs